Customer Relationship Model, Inovation and E-Commerce to Improving SME Marketing Performance in Pekanbaru - Siti Hanifa Sandri; Wan Laura Hardilawati (Akuntansi & Ekonomika, 2019)
UKM is one of the economic support in Indonesia. SMEs are required to have a competitive advantage and be able to improve marketing performance by maintaining long-term relationships with customers and increasing innovation in various sectors. Transactional marketing or traditional marketing must be updated with a new marketing system in the form of customer relationship marketing. The Industrial Revolution 4.0 is also a big challenge for SMEs to be able to improve their marketing performance and are demanded to be closer and faster to serve customers by utilizing e-commerce. The specific target of this research is to find out the marketing strategies carried out by SMEs in the city of Pekanbaru. This study uses quantitative research methods using Structural Equation Model (SEM). The results showed that the customer relationship marketing strategy did not have a significant effect on improving marketing performance, this was due to the fact that it was still not maximal and limited knowledge from SMEs. Innovation and E-commerce strategies have a significant effect on improving marketing performance. this can be a consideration for businesses to adobtinnovation and e-commerce strategy to compete amid the high growth and development of SMEs, especially in the culinary field in Pekanbaru.